Macrophages in inflammation, repair and regeneration. (25th August 2018) - Oishi, Yumiko; Manabe, Ichiro
Abstract: Tissue injury triggers a complex series of cellular responses, starting from inflammation activated by tissue and cell damage and proceeding to healing. By clearing cell debris, activating and resolving inflammation and promoting fibrosis, macrophages play key roles in most, if not all, phases of the response to injury. Recent studies of the mechanisms underlying the initial inflammation and later tissue regeneration and repair revealed that macrophages bridge these processes in part by supporting and activating stem/progenitor cells, clearing damaged tissue, remodeling extracellular matrix to prepare scaffolding for regeneration and promoting angiogenesis. However, macrophages also have a central role in the development of pathology induced by failed resolution (e.g. chronic inflammation) and excessive scarring. In this review, we summarize the activities of macrophages in inflammation and healing in response to acute injury in tissues with differing regenerative capacities. While macrophages lead similar processes in response to tissue injury in these tissues, their priorities and the consequences of their activities differ among tissues. Moreover, the magnitude, nature and duration of injury also greatly affect cellular responses and healing processes. In particular, continuous injury and/or failed resolution of inflammation leads to chronic ailments in which macrophage activities may become detrimental.